Sharing Short Stories With Children in EFL Classrooms: A Way to Achieve Success in EFL Education - Amparo Clavijo Olarte (Asociación Colombiana de Profesores de Ingles, 2016)
The purpose of this paper is to share some experiences teaching literature studies with children of third, fourth and fifth grades in a private school in Bogotá to demonstrate that English can be taught through the exploration of literature. The opportunity to offer learners a chance for literacy through reading stories is rewarding when you witness the joy children feel when opening a colorful book full of surprises and beautiful illustrations.